Kahramanmaraş Havzası’nın jeomorfolojisi - Korkmaz, Hüseyin (My University, 2000)
Kahramanmaraş basin was of appearance of transition in view of geographic position and geomorphological properties. It was located just in the southern part of intersection point of the Anatolia and Arabia salbs. For this reason, it retlects the intersection effects of these two salbs. In the basin, in the erea starting from Precambrian to Quaternary, a diversity developed in different facies and a stowage showing a disorder existed. This layer formed a quite complex structure being twisted and cracked because of the effect of serious tectonism continuing from, especially, Miocene to mouadap. In the basin, the oldest orogeneze traces were seen in the core units of the North Amanos Mountains. Caledonian and Hersinien orogenze affected these units. Alp Orogenze became effective in the whole basin in the from term. At the result of intersection of Arabia and Anatolia slaben in the bellow and middle maestrich, compressional stress directed to the north and south became effective in the basin. Because of this stress, allocation units located in upper Kretase by loading to basin from north. The basin gainet its main structural properties by this loading. This loading ocarried at the early Alpin term, caused to imprecate, crake, twist and imprecate on the Pre Alpin formation of the North Amanos Mountains. The North - South directed compresional stress extending from upper Kretase to upper Miocene faced the imprecate, loading and faults in the basin. In the upper Miocene, this stress caused to from death sea and the Eastern Anatolia faults having side base. The roof of graben forming the present basin came out by the effective of side faults and the other occurring at the same time. By the effective of Neotektonism contouring from upper Miocene to Quaternary also, the basin had gained current geomorphologic properties. Thus, two big geomorphologic units, the basin of basin and its around, developed. Among these, at the base of basin, Narly, Türko?lu, Mara? plaes; secondary horst featured plateau distinguishing these pleas from each other and lower swell areas exist. The around of the basin, consists of the North Amanos, Ba?konu? - Kubaly, Ahyr, Kartalkaya, mountains and hilly areas and plateus in the various altitude steps. In the developing of present relief in Kahramanmara? basin, as well as tectonic events, the common effects of climatic, hydrographic, vegetative and pedeologial factors also exist. The current properties of Kahramanmara? basin formed the problems for human activities in some areas. These problems showed differencies at the base of basin and the somewhat higher areas in its around. While floods, slugs and drawn out formed the most important problems in the plains at the base of basin, the main problems of high areas were erosion and soil motion. The earthquakes are common problems of all the basin. Active systems such as death sea and Eastern Anatolia faults increased the risk of earthquake. Residence's in the basin were generally centralised on alluviums around resources ranging through these fault lines. Since houses in here were far away from standard structure required for an active fault region, even dameges to be arised from an earthquake with middle degree might reach very important dimensions.

Kahramanmaraş Havzası, coğrafi konumu ve jeomorfolojik özellikleri ile bir geçiş kuşağı görünümündedir. Anadolu Levhası ile Arabistan Levhası'nın çarpışma sınırının hemen güneyinde yer alması, morfotektonik açıdan bu iki levhanın çarpışma etkilerini yansıtır. Havza'da Prekambrien'den Kuaterner'e kadar ki dönemde, değişik fasiyeslerde gelişmiş çeşitlilik ve karmaşıklık arz eden kalın bir istif bulunur. Bu istif, bilhassa Miosen'den günümüze kadar süregelen şiddetli tektonizma etkisiyle kıvrılarak ve kırılarak oldukça karmaşık bir yapı oluşturmuştur. Havza'da en eski orojenez izleri batıdaki Kuzey Amanos Dağları'nın çekirdek birimlerde görülür. Kaledonien ve Hersinien orojenezi bu birimleri etkilemiştir. Alp orojenezi ise safhalar halinde Havza'nın tamamında etkili olmuştur. Arabistan ile Anadolu Levhaları'nın Alt - Orta Maestrichtien'de çarpışması sonucunda Havza'da kuzey - güney yönlü kompresyonel stres etkili olmaya başlamıştır. Bu stres Üst Kretase'de allokton birimlerin Havza'ya kuzeyden bindirme ile yerleşmesine neden olmuştur. Havza ana yapısal özelliklerini bu bindirme ile kazanmıştır. Erken Alpin döneminde gerçekleşen bu bindirme, Kuzey Amanos Dağları'ndaki Pre Alpin Formasyonları'nda kıvrılma, kırılma ve ekaylanmalara yol açmıştır. Üst Kretase'den Üst Miosen'e kadar kuzey - güney yönlü kompresyonel stres, Havza'da kıvrımlar, bindirmler ve faylarla karşılanmıştır. Üst Miosen'de ise bu stres yanal atımlı Ölü Deniz ve Doğu Anadolu Fayları'nın oluşmasına neden olmuştur. Bu yanal atımlı faylar ile eş zamanlı oluşan diğer fayların da etkisiyle bugünkü Havza tabanını oluşturan grabenin çatısı ortaya çıkmıştır. Üst Miosen'den Kuaterner'e kadar süren şiddetli Neotektonizma'nın da etkisiyle Havza bugünkü jeomorfolojik özelliklerini kazanmıştır. Böylece Havza tabanı ve çevresi olmak üzere iki büyük jeomorfolojik ünite gelişmiştir. Bunlardan Havza tabanında; Narlı, Türkoğlu, Maraş Ovaları ile bunları birbirinden ayıran tâli horst özelliğindeki plato ve alçak eşik sahaları yer alır. Havza çevresi ise Kuzey Amanos, Başkonuş - Kubalı, Ahır, Kartalkaya Dağları ve tepelik alanlar ile çeşitli yükselti kademelerindeki platolardan oluşur. Kahramanmaraş Havzası'nda bugünkü rölyefin gelişiminde tektonik olayların yanında klimatik, hidrografik, vejetatif ve pedeolojik faktörlerin de ortak etkileri vardır. Kahramanmaraş Havzası'nın bugünkü jeomorfolojik özellikleri bazı alanlarda beşeri faaliyetler için problemler oluşturmaktadır. Bu problemler Havza tabanı ile çevresindeki nisbeten yüksek alanlarda farklılıklar göstermektedir. Havza tabanındaki ovalarda taşkınlar, bataklıklar, çekikler en önemli problemleri oluştururken, yüksek sahaların ana probleminin başında toprak erozyonu ile heyelânlar gelir. Depremler tüm Havza'nın ortak problemidir. Ölü Deniz ve Doğu Anadolu Fayı gibi aktif sistemlerin Havza içinden geçmesi deprem riskini artırmaktadır. Havza'daki yerleşmeler genelde bu fay hatları boyunca sıralanan su kaynakları etrafındaki alüvyonlar üzerinde toplanmıştır. Buradaki konutların ise aktif bir fay kuşağında olması gereken yapı standartlarından çok uzak oluşu, orta şiddette bir depremin yol açacağı zararları oldukça önemli boyutlara ulaştırabilir.
Keywords: Jeoloji; Jeomorfoloji; Jeomorfoloji-Türkiye-Kahramanmaraş